Improved efficiency of liquid-phase shear exfoliation of expanded graphite with mica plates as bifunctional additives. Issue 48 (2nd December 2021) - Liang, Bin; Liu, Kangwei; Liu, Peng; Zhao, Guangyao; Pan, Weisheng; Hu, Shengyu; Cui, Yuanzheng
Abstract : Liquid-phase shear exfoliation (LPSE) is a potential method of large-scale production of good-quality graphene. Abstract : Liquid-phase shear exfoliation (LPSE) is a potential method of large-scale production of good-quality graphene. Obtaining few-layer (<10) graphene with large lateral sizes and high yields remains a challenging issue. Here, we report an improved LPSE processing method involving the addition of mica plates, which serve as bifunctional agents. With the addition of 100 g L −1 of mica, the LPSE (9000 rpm/0.24 mm/1 h) of expanded graphite offers ∼100% few-layer graphene with average lateral sizes (ALSs) of ∼2.8 μm and yields of up to 27% (the highest ever reported). The graphene produced by LPSE without any additives, however, contains only ∼77% few-layer nanosheets, and has ALSs of ∼1.3 μm and yields of 8%. Significantly, the addition of SiO2 microspheres as a comparison has almost no influence on the LPSE. The mica plates control the vector of fluids in LPSE and guide the oriented arrangement of the layered materials ( e.g., expanded graphite), leading to significantly improved LPSE efficiency. 2D transition metal dichalcogenides (TMDs) with improved yields were also successfully prepared using LPSE with the addition of mica.